Moving Together to Make Lerep Village in Semarang Regency Safe from Sexual Violence - Rofi Wahanisa; Rahmawati Prihastuty; Pradipta Christy Pratiwi; Dyah Ayu Rahmawati; Moh Iqbal Mabruri; Santi Rohmawati; Inge Widya Pangestika; Adiyatma, Septhian Eka (Universitas Negeri Semarang, 2024)
Sexual violence against children in Central Java shows the highest percentage among other types of violence at 46.6%, while sexual violence against women is at 14.7%. This high incidence of violence is an important concern, especially in Semarang Regency, which is ranked third in Central Java. Sexual violence is vulnerable in public places, such as tourist attractions. Although cases of sexual violence that occur in Lerep Tourism Village have not yet surfaced, preventive efforts to prevent sexual violence against women and children need to be intensified. The solution offered through this community service proposal is the implementation of psychoeducation for youth organizations in Lerep Village related to sexual violence. This program is in line with the 8th mission of Lerep Village in efforts to provide services, protection, and social empowerment for vulnerable groups, the poor, the elderly, orphans / orphans, people with disabilities and pregnant women. Therefore, psychoeducation on sexual violence and types of sexual violence, knowledge about healthy relationships and handling sexual violence both legally and psychologically was prepared. This psychoeducation also aims to equip teenagers in Lerep Village who are engaged as agents of change in an effort to prevent sexual violence and handle it if it occurs in the Lerep tourist village.